Study of load spectrum compilation method for the pantograph upper frame based on multi-body dynamics. (May 2022) - Mei, Guiming; Luo, Qun; Qiao, Wei; Huang, Zhong; Lu, Jing; Wang, Jiangwen
Highlights: Established PCS model to obtain random loads on the pantograph upper frame. Polynomial fitting to get hazard point stress of concern spectrum and verification. Upper frame full life load spectra were prepared by KDE extrapolation. The practicality of accelerated fatigue load spectrum verified in test bench. Abstract: This paper proposed a fatigue test load spectrum compilation method for key pantograph components to study the reduction of the pantograph development cycle and optimization of its structural design to ensure the service reliability of pantographs. This paper established a pantograph-catenary coupling dynamics model to obtain the stochastic load-time histories with the upper frame of a modern high-speed pantograph as the research object. The stress load spectrum of the pantograph upper frame was obtained using finite element simulations with polynomial fittings. This paper proposed an extrapolation method for the rainflow count matrix of the stress load spectrum based on the two-dimensional kernel density estimation theory. This paper applied the equivalent damage criterion, gave the load back-propagation method, and further obtain the accelerated load spectrum, and verified the load spectrum by designing the bench test for fatigue test. The results showed that the accelerated load spectrum obtained by back-propagation can retain the complete load characteristics of the original spectrum and accurately simulate the combined load effect under the actual use of the pantograph. This method improves the accuracy and efficiency of accelerated life testing of pantograph components and provides a reference basis for the subsequent development of reliability design, accelerated life testing, and life prediction of key pantograph components.